Temperature-dependent decyclopolymerization of cyclic oligomers and the implication on destructuring layered nanosheets for nanocomposite reinforcement - Hong, Sung Chul; Lee, Sang-Soo (ELSEVIER SCI LTD, 2013)
Taking advantages of low viscosity, self-consistent stoichiometry and explosive decyclopolymerization of cyclic butylene terephthalate oligomers (CBTs), the destruction of multi-layered silicate nanosheets of organically modified montmorillonite (OMMT) has been attempted to explore the reinforcing effect on polymer matrix. Because of the molecular weight and the viscosity imparted by cyclic structure, CBTs were successfully embedded into OMMT galleries, as evidenced by XRD presenting a large down-shift of basal plane peak along with decrease of peak intensity. Subsequent decyclopolymerization of CBTs in-between silicate nanosheets of OMMT has been found governed by polymerization temperature; when a poly(CBT) of high molecular weight is obtainable, efficient dissociation of OMMT to silicate nanosheets and their homogeneous dispersion allowing a notable increase of energy absorption for failure are yielded. A dissociation of OMMT mediated by the temperature-dependent decyclopolymerization presents the usability of cyclic oligomers in the formation of thermoplastic polymer-based nanocomposites exhibiting effective reinforcement which can be hardly accomplished through a conventional process. (c) 2013 Elsevier Ltd. All rights reserved.
Keywords: RING-OPENING POLYMERIZATION; POLY(BUTYLENE TEREPHTHALATE) NANOCOMPOSITES; PET-CLAY NANOCOMPOSITES; IN-SITU POLYMERIZATION; 1,2-DIBENZOYLBENZENE MOIETY; MELT INTERCALATION; KETONE OLIGOMERS; MORPHOLOGY